Independent and joint associations of a body shape index and cardiorespiratory fitness with executive function in adolescents: a cross-sectional study in China - Bi, Cunjian; Ran, Xiaokang; Zhang, Feng; Ye, Xinming; Yin, Xiaojian; Zhang, Mengmeng; Sun, Pengwei (Frontiers in Nutrition, 2026)
BackgroundExecutive function plays a crucial role in adolescent development and future adult achievement. However, previous research on the associations between a body shape index (ABSI), cardiorespiratory fitness, and executive function has been limited. No studies have yet been conducted using nationally representative samples. This study aims to analyze the independent and joint associations among ABSI, cardiorespiratory fitness, with executive function using a national sample, thereby providing support for enhancing and intervening in executive function among Chinese adolescents.MethodsFrom 2022 to 2023, a three-stage stratified cluster sampling method was employed to randomly select 8,621 adolescents aged 13–18 years across nine regions in China for a cross-sectional assessment of ABSI, cardiorespiratory fitness, and executive function. The independent and joint associations between ABSI, cardiorespiratory fitness, with executive function were analyzed using chi-square tests, t-tests, one-way ANOVA, binary logistic regression, and generalized linear model binary logistic regression.ResultsThe VO2max of Chinese adolescents is (41.12 ± 5.08) mL/kg/min; the ABSI is (0.0615 ± 0.0240). The inhibit control function reaction time, the refreshing memory function reaction time, and the switching flexibility function reaction time are (13.69 ± 11.89) ms, (1055.05 ± 354.69) ms, and (320.32 ± 182.66) ms, respectively. Compared across the ABSI groups (Q1, Q2, Q3, Q4), statistically significant differences were observed in reaction times for the adolescent inhibit control function, refreshing memory function, and switching flexibility function (χ2 = 72.642, 184.613, 2826.466, p < 0.001). Similarly, statistically significant differences were observed in VO2max between Q1, Q2, Q3, and Q4 groups (χ2 = 54.539, 47.333, 42.127, p < 0.001). Generalized linear model binary logistic regression analysis revealed that compared with the group with ABSI is Q1 and VO2max is Q4, the group with ABSI is Q3 and VO2max is Q1 exhibited a higher risk of developing: refreshing memory function dysfunction (OR = 6.20, 95% CI: 4.42–8.70), and switching flexibility function dysfunction (OR = 4.76, 95% CI: 3.48–6.52; p < 0.001).ConclusionThere are independent and joint associations between ABSI, cardiorespiratory fitness and executive function among Chinese adolescents. Effectively controlling the increase in ABSI and improving cardiorespiratory fitness levels play a positive role in promoting executive function in adolescents.